A preliminary microbial study of the dental handpieces used in the UPCD - Ng, Marie Edlynn F.; Esteban, Maria Concepcion R.; Caparas, Lourdes (Adviser).
20 handpieces were swabbed before and after disinfection by either 1:750 Zephiran Chloride or 70% Isopropyl Alcohol. The swabs were then cultured to determine the gram reaction, morphology and hemolytic activity of the bacteria present and be able to assess if there is significant difference between the sterilizing effect of Zephiran Chloride and Isopropyl Alcohol.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Dental instruments and apparatus